Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1002/anie.200461392
|View full text |Cite
|
Sign up to set email alerts
|

A Bis(thiophosphinoyl)methanediide Palladium Complex: Coordinated Dianion or Nucleophilic Carbene Complex?

Abstract: A question of identity: A palladium complex featuring a carbenic S,C,S‐based pincer ligand is reported (see scheme). DFT calculations show that, unlike classical carbene complexes, coordination occurs through donation from a d orbital at the metal into the empty np orbital of the carbene fragment, with the nσ orbital essentially acting as a nonbonding orbital. The complex is shown to have nucleophilic character.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 119 publications
(72 citation statements)
references
References 43 publications
(12 reference statements)
5
67
0
Order By: Relevance
“…Leung and co-workers have shown that the reaction of SnCl 4 with the magnesium reagent MgC(PPh 2 S) 2 (THF) 2 produces the tin(IV) complex Sn[C(PPh 2 S) 2 ] 2 , in which the ligand is bonded in a tridentate (S,C,S) fashion to tin. [10] Interestingly, in this work we isolated small amounts of complex 1b from the reaction of the dilithium reagent Li 2 2 ] (EЈ = S, Se) via chalcogen insertion into Pb-C bonds has been reported previously by Leung et al [11] The 31 P NMR spectra of 1b and 1c in CD 2 Cl 2 show a single resonance at δ = 54.9 and 57.6 ppm, respectively, cf. δ = 61.6 for 1a in CD 2 Cl 2 .…”
Section: Synthesis and Nmr Spectra Of Sn[eјc(pph 2 E) 2 ] 2 [E = Eј =mentioning
confidence: 67%
See 4 more Smart Citations
“…Leung and co-workers have shown that the reaction of SnCl 4 with the magnesium reagent MgC(PPh 2 S) 2 (THF) 2 produces the tin(IV) complex Sn[C(PPh 2 S) 2 ] 2 , in which the ligand is bonded in a tridentate (S,C,S) fashion to tin. [10] Interestingly, in this work we isolated small amounts of complex 1b from the reaction of the dilithium reagent Li 2 2 ] (EЈ = S, Se) via chalcogen insertion into Pb-C bonds has been reported previously by Leung et al [11] The 31 P NMR spectra of 1b and 1c in CD 2 Cl 2 show a single resonance at δ = 54.9 and 57.6 ppm, respectively, cf. δ = 61.6 for 1a in CD 2 Cl 2 .…”
Section: Synthesis and Nmr Spectra Of Sn[eјc(pph 2 E) 2 ] 2 [E = Eј =mentioning
confidence: 67%
“…Although heteroleptic complexes with In III [5] and Te IV , [6] as well as monomeric Pb II derivatives, [11] were previously known, the Sn IV examples 1b and 1c represent the first homoleptic complexes of these interesting ligands with p-block metals or metalloids. However, the low isolated yields and detection of the diselenide [{Li(tmeda)}{SeC(PPh 2 S) 2 2-(EЈ = S, Se) with CuCl 2 . [7,8,9] Experimental Section General Procedures: All reactions and manipulations were carried out in an argon atmosphere by using standard Schlenk techniques.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations